2015
DOI: 10.1080/01616412.2015.1114742
|View full text |Cite
|
Sign up to set email alerts
|

Swimming does not alter nociception threshold in obese rats submitted to median nerve compression

Abstract: In conclusion, swimming, a conservative treatment for peripheral nerve lesions, was not able to improve the nociception threshold in obese rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Actually, obese prediabetic mice showed higher levels of GDNF and NGF in nerves and spinal cord [695]. In contrast, swimming does not alter nociception threshold in obese rats submitted to median nerve compression [696]. Regarding human studies, it has been suggested that increased physical exercise has no mitigating effects on low back pain in obese subjects [49], but further studies on the beneficial effects of physical exercise are needed to obtain robust conclusions on pain modulation on obese subjects.…”
Section: Pathological Pain: Relationship With Sedentary Behavior and ...mentioning
confidence: 99%
“…Actually, obese prediabetic mice showed higher levels of GDNF and NGF in nerves and spinal cord [695]. In contrast, swimming does not alter nociception threshold in obese rats submitted to median nerve compression [696]. Regarding human studies, it has been suggested that increased physical exercise has no mitigating effects on low back pain in obese subjects [49], but further studies on the beneficial effects of physical exercise are needed to obtain robust conclusions on pain modulation on obese subjects.…”
Section: Pathological Pain: Relationship With Sedentary Behavior and ...mentioning
confidence: 99%
“…The studies included rats (26 studies) [ 21 29 , 32 – 38 , 40 42 , 45 47 , 51 , 52 , 56 , 58 ], mice (13 studies) [ 20 , 30 , 31 , 39 , 44 , 48 50 , 53 – 55 , 57 , 59 ] or rabbits (1 study) [ 43 ]. Sprague Dawley rats (18 studies) [ 21 , 24 29 , 32 , 35 – 38 , 40 , 42 , 47 , 51 , 52 , 56 ], C57BL/6J mice (8 studies) [ 20 , 30 , 31 , 39 , 48 , 53 , 57 , 59 ] and Wistar rats (7 studies) [ 22 , 23 , 33 , 34 , 41 , 45 , 58 ] were the most frequently used animal strains. Thirty studies exclusively used male animals [ 20 , 23 , 25 , 28 – 31 , 33 – 39 , 41 50 , 52 , 54 56 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other biomarkers, such as neurotrophins and neurotransmitters are also modulated by exercise. Of note, studies which did not demonstrate an effect on biomarkers used exercise duration of less than 40 minutes, 29 , 31 perhaps insufficient time to generate changes. In contrast, studies showing an effect on biomarkers included sessions with a duration between 60 and 90 minutes.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 Only 1 article found no post-treatment differences in BDFN concentrations. 31 One paper found an increase of GAP-43 in the peripheral nerve. 31 …”
Section: Qualitative Analysismentioning
confidence: 99%